Evaluation of gamma irradition process for induction of color change in gel composite (Brazilian Journal of Radiation Sciences, 2021)
The gamma irradiation process of industrial and medical materials is based on radio-induced changes for specific purposes, such as sterilization or induction of color formation. In gem irradiation, for example, color changes according to the deposited dose. In this work we present results obtained by the irradiation of clinical gel/copper sulfate composite to observe the color change for further evaluation of its use as an indicator of volume dose distribution. The irradiations were performed with a Co-60 source at doses between 10-100 kGy in XXXXX of XXXXX. Samples were prepared in three different compositions in relation to the amount of copper sulfate added (100, 400 and 500 mg of CuSO4 in 100 ml of clinical gel). Samples were photographed before and after exposure and color change evaluated with the ImageJ© program. Was observed color change in the samples as the radiation dose increase. Greater color variations were observed for the sample of clinical gel/CuSO4 (100 mg). The samples were re-evaluated one month after irradiation and it was noticed that the color undergoes alteration over time, but without returning to the original color. These results are useful in characterizing future use of the composite as a volumetric indicator of dose distribution in gamma irradiation processes.